2020
DOI: 10.1017/s0007114520001853
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory potential in relation to the gut microbiome: results from a cross-sectional study

Abstract: Abstract Diet has direct and indirect effects on health through inflammation and the gut microbiome. We investigated total dietary inflammatory potential via the literature-derived index (Dietary Inflammatory Index (DII®)) with gut microbiota diversity, composition and function. In cancer-free patient volunteers initially approached at colonoscopy and healthy volunteers recruited from the medical centre community, we assessed 16S ribosomal DNA in all sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 79 publications
4
46
2
Order By: Relevance
“…Conversely, the plant-based diet has been linked with producers of short chain fatty acids (SCFA) [ 60 ], by-products of gut microbiota that have anti-inflammatory properties [ 61 ]. Furthermore, a study has also shown that a lower DII score was associated with anti-inflammatory gut microbiota and reduced inflammatory markers [ 52 , 62 ]. Altogether, this may explain the protective effect of an anti-inflammatory, healthy and plant-based diet towards obesity by preventing inflammation through gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the plant-based diet has been linked with producers of short chain fatty acids (SCFA) [ 60 ], by-products of gut microbiota that have anti-inflammatory properties [ 61 ]. Furthermore, a study has also shown that a lower DII score was associated with anti-inflammatory gut microbiota and reduced inflammatory markers [ 52 , 62 ]. Altogether, this may explain the protective effect of an anti-inflammatory, healthy and plant-based diet towards obesity by preventing inflammation through gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Roseburia hominis and inulinivorans were enriched in non-smokers. These bacteria all produce butyrate and SCFAs, which break down polysaccharides and reduce inflammation (Chu et al, 2019;Ticinesi et al, 2020;Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation has shown that one mechanism by which BRB accomplish this change in gut metabolism is through the ability of BRB to selectively increase Akkermansia muciniphila within the colon (Tu et al., 2020). As the Akkermansia muciniphila species is associated with decreased inflammation systemically in humans, it is considered a positive microbe in the context of cancer (Meng, Zhang, Wu, Yu, & Fang, 2020; Zheng et al., 2020).…”
Section: Resultsmentioning
confidence: 99%